System gospodarczy Iraku - Kalal, Muiead A. (Wydział Prawa i Administracji UAM, 1986)
Both natural resources and planned economy contributed to the economic achievements of Iraq manifested by a high, exceeding 25% rate of economic growth (GNP) in the years 1975 -1980. Exports of the most important product of the extractive, industry-which is oil-have the crucial importance for the country's economy. Yet the economy is not entirely concentrated on that industry. The first place in investment expenditures, in economic programs is occupied by the development of manufacturing industry, which share in the 1982 GNP was up to 18%. The investments in agriculture are also not neglected. The State plays the vital part in the economic system of Iraq. It is controlling the production and development according to the State economic programs. The State's share in the production is also large on account of the existence of the State enterprises which replaced the foreign capital in the extracting industry. The dominating part of the national income (approximately 70%) is generated by the State enterprises. Alongside, there are private producers operating and mixed enterprises with the capital share of State and private persons., State firms private and mixed companies are pursuing the market economy. The State financial policies are oriented to control all the enterprises by means of taxation policy as well as credit policies of banks which are State owned in Iraq, not to mention the State price ruling. Thus the economic system of Iraq seems to be a combination of the plan economy and State controlled market economy
The Economic System of Iraq